Rock Mechanics Characteristics Test and Optimization of High-Efficiency Mining in Dajishan Tungsten Mine. (13th August 2018) - Zhao, Kang; Gu, Shuijie; Yan, Yajing; Li, Qiang; Xiao, Wanqi; Liu, Guoqing
Abstract : Rock mechanics test is not only the basis for obtaining the mechanical parameters of rock but also an important means for studying rock mechanics and engineering. In this paper, the uniaxial compression deformation test, Brazilian splitting test, and cornea pressure shear test are carried out for rocks in the Dajishan tungsten mine. The basic mechanical parameters such as uniaxial compressive strength, tensile strength, elastic modulus, Poisson's ratio, and internal friction angle of ore rock and surrounding rock are obtained. Meanwhile, damage characteristics of rock are deeply studied and analyzed under different experimental conditions. According to rock mechanics parameters which are obtained from indoor rock mechanics tests, three design schemes of stope structure parameters are optimized by using the FLAC 3D numerical simulation software. On the premise of ensuring the stability of the stope structure, the recovery rate of ore and the production capacity of the stope are taken into consideration. It is suggested that the second scheme should be adopted for mines (18 m for ore room and 7 m for ore pillar), which provides scientific guidance for the safe and efficient mining of mines.